Semiconductor Materials and Devices for High Efficiency Broadband and Monochromatic Photovoltaic Energy Conversion - Beattie, Meghan (Université d'Ottawa / University of Ottawa, 2021)
This thesis addresses barriers to the widespread adoption of high-efficiency photovoltaic devices through the use of innovative semiconductor materials and device design. The feasibility of various strategies is explored through experimental characterization and modeling of semiconductor materials and devices. High-efficiency photovoltaic devices are made from epitaxially grown III-V semiconductor materials. Epitaxial devices are highly sensitive to lattice mismatch between the epi-layers and the substrate, requiring sophisticated substrate engineering or growth strategies to access materials outside of the lattice-matched regime. One promising strategy involves the electrochemical porosification of germanium on a lattice-mismatched silicon substrate to create a compliant interface for high-quality epitaxial growth of Ge, GaAs, and other equivalent-bandgap III-V semiconductors on silicon. This results in a threading dislocation density of ~10^4 cm^-2, a reduction of 4 to 6 orders of magnitude compared to direct epitaxy of germanium on silicon. This technology could enable the development of highly efficient III-V multi-junction photovoltaic devices on cost-effective silicon substrates that benefit from well-established commercial supply chains. In the first part, I present characterization of the electrical properties of porous germanium. Experimental measurements revealed conductivities ranging from 0.6 to 33 (x10^-3) Ohm^-1 cm^-1, depending on the morphology. The relationship between the electrical properties and the morphology is described using an electrostatic model that can be generalized to other porous semiconductors including silicon. For a compliant interface designed to integrate a standard triple-junction solar cell onto a silicon substrate, the porous Ge/Si layers are predicted to introduce < 0.01 Ohm cm^2 of series resistance to the device, which is sufficiently low for concentrated photovoltaic applications. Optoelectronic device modelling of the triple-junction solar cell on silicon demonstrates that III-V triple-junction solar cells fabricated on silicon using this compliant Ge/Si porous interface could achieve 93% of the efficiency of a comparable defect-free device. The remainder of this thesis is concerned with the design and characterization of photovoltaic devices optimized for monochromatic illumination, known as photonic power converters. Most commercially available photonic power converters are based on GaAs and are suitable for short-range photonic power transmission through optical fiber (< 1 km). Extended reach power-over-fiber systems require the use of photonic power converters that are compatible with longer-wavelength light, which travels further in optical fiber. One candidate material for this application is the semiconductor quaternary alloy InAlGaAs lattice-matched to InP for photonic power converter operation in the telecommunications O-band, near 1310 nm. I describe the design and characterization of multi-junction InAlGaAs/InP photonic power converters grown by molecular beam epitaxy, including the analysis of material properties and characterization of single- and dual-junction devices under 1319-nm laser illumination. Optically thick devices are found to be diffusion-limited and device simulations suggest that non-radiative recombination is significant. The performance of InAlGaAs tunnel diodes, which act as interconnections for the absorbing junctions within a multi-junction device, is demonstrated to be highly dependent on the growth temperature, with peak tunneling current densities exceeding 1200 A/cm^2 in the best measured devices. In addition to molecular beam epitaxy-grown InAlGaAs/InP devices, I also characterize single-junction O-band photonic power converters grown by metal-organic vapour phase epitaxy with two alternative absorber materials. A lattice-matched InGaAsP/InP device is compared to a more cost-effective lattice-mismatched GaInAs device grown on GaAs using a metamorphic buffer layer. Both devices are measured under 1319-nm laser illumination with a variety of beam sizes and peak efficiencies of 52.9% and 48.8% were measured for the InGaAsP/InP and the metamorphic-GaInAs/GaAs devices respectively. At illumination powers exceeding 100 mW, the performance begins to degrade with increasingly non-uniform illumination, indicating that illumination profiles should be as uniform as possible to maximize device performance.
Keywords: Photovoltaics; Photonics; Power-over-fiber; Solar energy; III-V semiconductors; Porous germanium; Photonic power converter